MOLECULAR DOCKING OF LION’S MANE BIOACTIVE COMPOUNDS AS BETA-SECRETASE INHIBITORS FOR ALZHEIMER’S DISEASE - NOURA BERAKDAR; SUNDUS J YASEEN; AZHAR MALEK; MOHMAD EIAD ALRAAI (Innovare Journal of Life Sciences, 2025)
Objectives: Lion’s Mane is a medicinal mushroom that has attracted significant interest due to its proposed neuroprotective activity. This has led to research into its potential uses in neurological diseases such as Alzheimer’s. Alzheimer’s disease is a neurodegenerative disease characterized by a progressive decline in mental function. Pathologically, the disease is associated with the deposition of amyloid-beta plaques and neurofibrillary tangles within the brain. Beta-secretase is a key enzyme in the amyloid genesis pathway. Therefore, beta-secretase is considered a promising therapeutic target to halt the development and progression of Alzheimer’s disease. Purpose: This research aims to explore the effect of the active compounds hericinone present in Lion’s Mane mushroom as a beta-secretase inhibitor by performing the docking process using Molegro Virtual Docker. Methods: This study conducted a docking study of beta-secretase and some hericinones. Among them, the optimal binding energy of hericinones B was determined after meeting the drug-drug similarity criteria. Results: The binding energy of the target beta-secretase to hericinone B was calculated to be −168 kcal/mol. This energy compares favorably with the binding energy of known ligand complexes to the target, which is −164 kcal/mol. The docking process involving the selected beta-secretase enzyme (Protein Data Bank ID-5QCU) was performed using Molegro. This process is consistent with the five Lipinski guidelines and demonstrates the drug’s likelihood and bioavailability. Conclusion: Hericinone B was found to be the best compound that achieved better inhibition energy than the basic ligand. This is due to its chemical structural characteristics, its combination of lipophilic and polar regions, its hydrogen bonding ability, and the specific spatial arrangement of functional groups, which likely allows it to bind to a specific target.